Anxiolytic Effects of Nutritional Strategies in Craniofacial Inflammatory Conditions: A Scoping Review - Yusuf, Hajrah; Mukhtar Nur Anam (YARSI Dental Journal, 2025)
Introduction: Craniofacial inflammatory conditions, such as temporomandibular joint disorders and periodontitis, are often linked to heightened anxiety-like responses. Emerging evidence suggests that nutritional strategies may serve as effective, non-pharmacological approaches to mitigate anxiety under such conditions. Objective: To systematically review the evidence on the anxiolytic effects of dietary strategies, such as omega-3 fatty acids, magnesium, probiotics, and curcumin, in individuals or animal models experiencing craniofacial inflammatory conditions. Methods: PubMed, Scopus, and Web of Science were systematically searched for studies published up to January 2025. Studies were included if they evaluated the impact of nutritional interventions on anxiety outcomes in populations with craniofacial inflammation. Relevant data on the study population, interventions, and outcomes were extracted and summarized. Review/Discussion: Five studies were included, comprising human and animal research. Omega-3 fatty acids and magnesium supplementation were associated with reduced anxiety scores and inflammatory markers. Probiotics showed improvement in psychological symptoms and systemic inflammation. Curcumin demonstrated anxiolytic effects by reducing oxidative stress, with combined omega-3 and curcumin showing synergistic benefits. Despite promising results, significant variability in methodologies and outcome measures limits the generalizability of findings. Conclusion: Nutritional strategies hold promise for reducing anxiety in craniofacial inflammatory conditions. Further research with standardized protocols is needed to validate these findings and inform clinical applications.